2015
DOI: 10.1007/s00429-015-1005-z
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein Celf6 is highly expressed in diencephalic nuclei and neuromodulatory cell populations of the mouse brain

Abstract: The gene CUG-BP, Elav-like factor 6 (CELF6) appears to be important for proper function of neurocircuitry responsible for behavioral output. We previously discovered polymorphisms in or near CELF6 may be associated with autism spectrum disorder (ASD) in humans and that the deletion of this gene in mice results in a partial ASD-like phenotype. Here, to begin to understand which circuits might mediate these behavioral disruptions, we sought to establish in what structures, with what abundance, and at which ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…1 Behavioral impairments were observed in two tasks. 4 Specifically, robust expression of the protein was observed in the neuromodulatory transmitter-expressing nuclei, including noradrenergic and dopaminergic populations, and, as expected, 5-HT cells. Second, as adults, Celf6 −/− mice displayed a different response pattern compared to littermate controls in the holeboard task, a measure used to assess exploration and olfactory preference, and how they may be related to perseverative behavior.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…1 Behavioral impairments were observed in two tasks. 4 Specifically, robust expression of the protein was observed in the neuromodulatory transmitter-expressing nuclei, including noradrenergic and dopaminergic populations, and, as expected, 5-HT cells. Second, as adults, Celf6 −/− mice displayed a different response pattern compared to littermate controls in the holeboard task, a measure used to assess exploration and olfactory preference, and how they may be related to perseverative behavior.…”
supporting
confidence: 65%
“…1 Subsequent deep characterization of the temporal and spatial expression patterns of CELF6 RNA and protein in the brain showed these gene products are present early in a subset of neurons during neurodevelopment and into adulthood, peaking around birth. 4 Specifically, robust expression of the protein was observed in the neuromodulatory transmitter-expressing nuclei, including noradrenergic and dopaminergic populations, and, as expected, 5-HT cells. There was also robust expression in the hypothalamus, cholinergic cells of the striatum and other aspects of the limbic system.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…To define the in vivo binding locations of CELF6, we performed CLIP on brains from BAC transgenic mice expressing an epitope tagged CELF6-YFP/HA (78 kDa) with the endogenous CELF6 pattern (9). As CELF6 molecular function has not been studied in vivo, we first confirmed CELF6 binds RNA in the brain.…”
Section: Celf6 Primarily Associates With 3'utrs Of Target Mrnas In Vivomentioning
confidence: 98%
“…Our laboratory identified CELF6 as both enriched in serotonin producing neurons and disrupted in an individual with autism (8). Upon further study, CELF6 also showed enriched expression in the hypothalamus and in several monoaminergic cell populations commonly targeted for treatment in psychiatry (9). Functionally, CELF6 has been shown capable of regulating splicing in vitro (10), however its targets and function in vivo are uncharacterized.…”
Section: Introductionmentioning
confidence: 96%